2019
DOI: 10.2516/ogst/2019003
|View full text |Cite
|
Sign up to set email alerts
|

Role of divalent ions, temperature, and crude oil during water injection into dolomitic carbonate oil reservoirs

Abstract: Although wettability alteration has been shown to be the main control mechanism of Low Salinity and Smart Water (LS-SmW) injection, our understanding of the phenomena resulting in wettability changes still remains incomplete. In this study, more attention is given to direct measurement of wettability through contact angle measurement at ambient and elevated temperatures (28 °C and 90 °C) during LS-SmW injection to identify trends in wettability alteration. Zeta potential measurement is utilized as an indirect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The Zp of colloidal dispersions was measured using laser Doppler electrophoresis (LDE). In the LDE, a voltage across a cell is used, and the electrophoretic mobility of particles is obtained from the frequency shift observed in the scattered light 67,68 . The electrophoretic mobility measure is the best and simplest manner to estimate the Zp 69 .…”
Section: Methods Brine Compatibility Studies and Determining The Most...mentioning
confidence: 99%
See 2 more Smart Citations
“…The Zp of colloidal dispersions was measured using laser Doppler electrophoresis (LDE). In the LDE, a voltage across a cell is used, and the electrophoretic mobility of particles is obtained from the frequency shift observed in the scattered light 67,68 . The electrophoretic mobility measure is the best and simplest manner to estimate the Zp 69 .…”
Section: Methods Brine Compatibility Studies and Determining The Most...mentioning
confidence: 99%
“…The Zp values were the average of three measurements for the sample. Potential determining ions including Ca 2+ , Mg 2+ , and SO 4 2− can importantly influence the interactions at the LSW/rock interface that straight effects the EDL in oil reservoirs 68 . These ions are attached to the rock surface and change the rock-brine interface charge 86 .…”
Section: Impact Of Dilution Salinity and Brine Composition On Rock Su...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies indicate that the efficiency of water flooding operations is highly dependent on the salinity and composition of the injection water. In fact, oil/brine/rock interactions and the oil recovery can be optimized by modification of the injection water salinity and ionic composition (Sohal et al 2016;Fattahi Mehraban et al 2019;Mokhtari et al 2019;Rostami et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Sheng reviewed that approximately 17 mechanisms pertaining to solely LSWF, among which fine migration, mineral dissolution, Multicomponent Ion Exchange (MIE), and wettability alteration stood as prominent [22]. Extensive works [23][24][25][26] presented comprehensive results regarding the effects of ion types on the effectiveness of LSWF. They found that SO 4 2À is the most dominant in driving rock to less oil wetness.…”
Section: Introductionmentioning
confidence: 99%